SAT0510 LONG-TERM EFFECTIVENESS OF CANAKINUMAB IN AID – INTERIM ANALYSIS OF THE CAPS SUBGROUP FROM THE RELIANCE REGISTRY. (13th June 2020) - Blank, N.; Borte, M.; Foeldvari, I.; Horneff, G.; Kallinich, T.; Kortus-Goetze, B.; Oommen, P.; Schuetz, C.; Weller-Heinemann, F.; Weber-Arden, J.; Kuemmerle-Deschner, J. B.
Abstract : Background: In the treatment of monogenic autoinflammatory diseases (AID), a heterogeneous group of diseases with excessive interleukin (IL)-1β release and severe systemic and organ inflammation, the anti-IL-1 inhibitor canakinumab (CAN) has been associated with rapid remission of symptoms in clinical trials as well as in real-life. 1-3 Objectives: The aim of the RELIANCE registry is to explore long-term effectiveness and safety of CAN under routine clinical practice conditions in pediatric and adult patients with CAPS (cryopyrin-associated periodic syndromes, including Muckle-Wells syndrome [MWS], familial cold autoinflammatory syndrome [FCAS], neonatal onset multisystem inflammatory disease [NOMID]/chronic infantile neurological cutaneous and articular syndrome [CINCA]), FMF (familial Mediterranean fever), TRAPS (tumor necrosis factor receptor-associated periodic syndrome) and HIDS/MKD (hyperimmunoglobulinemia D syndrome/mevalonate kinase deficiency). Methods: This prospective, non-interventional, observational study is based in Germany with a 3-year follow-up and enrolls pediatric ≥2 years and adult patients with clinically confirmed diagnoses of CAPS, FMF, TRAPS and HIDS/MKD routinely receiving CAN. In 6-monthly visits, clinical data and patient-reported outcomes are assessed. Study endpoints are long-term effectiveness and safety of CAN. Here, the CAPS cohort was analyzed. Results: This 18-month interim-analysis includes 78 CAPS patients (49% females) enrolled by September 2019. Mean age at baseline was 25 years and mean duration of prior CAN treatment was 5.7 years. 64 patients (82%) had MWS, 2 FCAS, 7 NOMID/CINCA, 3 atypical CAPS and 2 lacked subtype diagnosis. Disease activity, fatigue and social impairment by patients' assessment, days absent from school/work, inflammatory markers, and remission by physician assessment were evaluated at 6-monthly intervals starting at baseline with last update at 18 months of follow-up (table 1 ). The results demonstrate sustained remission and disease control as evaluated parameters remained stable over time. Serious adverse events were reported for 9 patients including papillitis, pyrexia, tonsillitis (n=2), appendicitis, chest pain, circulatory collapse, skin disorders, and preterm delivery. Conclusion: The 18-month interim analysis of the RELIANCE study, the longest running real-life CAN registry, demonstrates that long-term CAN treatment is safe and effective in CAPS patients. References: [1]Lachmann et al. N Engl J Med. 2009;360(23):2416-25 [2]Kuemmerle-Deschner et al. Rheumatology (Oxford). 2016;55(4):689-96 [3]De Benedetti et al. N Engl. J Med. 2018;378(20):1908-1919 Disclosure of Interests: Norbert Blank Grant/research support from: Novartis, Sobi, Consultant of: Novartis, Sobi, Lilly, Pfizer, Abbvie, BMS, MSD, Actelion, UCB, Boehringer-Ingelheim, Roche, Michael Borte Grant/research support from: Pfizer, Shire, Ivan Foeldvari Consultant of: Novartis, Gerd Horneff Grant/research support from: AbbVie, Chugai, Merck Sharp & Dohme, Novartis, Pfizer, Roche, Speakers bureau: AbbVie, Bayer, Chugai, Merck Sharp & Dohme, Novartis, Pfizer, Roche, Tilmann Kallinich Grant/research support from: Novartis, Consultant of: Sobi, Roche, Novartis, Birgit Kortus-Goetze Consultant of: Novartis, Prasad Oommen Consultant of: Novartis, Catharina Schuetz: None declared, Frank Weller-Heinemann: None declared, Julia Weber-Arden Employee of: I am employed by Novartis, J. B. Kuemmerle-Deschner Grant/research support from: Novartis, AbbVie, Sobi, Consultant of: Novartis, AbbVie, Sobi